If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-7=12-(5x+7)
We simplify the equation to the form, which is simple to understand
7x-7=12-(5x+7)
Remove unnecessary parentheses
7x-7=12-5x-7
We move all terms containing x to the left and all other terms to the right.
+7x+5x=+12-7+7
We simplify left and right side of the equation.
+12x=+12
We divide both sides of the equation by 12 to get x.
x=1
| 84=5m+3(4m-6) | | 3x+8=11+2x | | 314=13(x-2)-(12x-13)+2(150+x) | | 8t-2=16(t-2.5) | | 2+2y=-6 | | 4x+3=12x-13 | | 1+3x=16-2r | | 6+9x=8x-12 | | 12h=10h | | 3-4x=44 | | 56x+2=42x+5 | | 5-8x=24 | | 4x-25=105 | | 5x-9=13x-(8x-4) | | 2x-4-5x+10=40 | | 3x+17=59 | | 4(2m+1)=3(2m-5) | | 40x+40=15x+30 | | 3x(2x-1)(x^2-9)(x^2+8)=0 | | 5x^2=3y | | 4x=22x+56 | | -8=32-8q | | 10(3-x)-4(6-8x)+1,5(4-10x)-26=0 | | 30-12x=26+4x | | 4t^2+7t-15=0 | | 4(2x-3)=23 | | 12z+7=67+9z | | 4(h-7)+4=-8 | | 2(c+10)-9=7 | | 5t-7+9t=4t-33 | | 6m-2=19-m | | 5(h-1)+6=-9 |